Beta acid extracts of hops have a modest effect on ruminal metabolism and apparent total tract digestibility by steers fed high- concentrate diets - Uwituze, S.; Heidenreich, J.M.; Higgins, James J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Hops have been used for centuries to control bacterial contamination in beer production. Today, alpha acids are extracted from hops for use in flavoring beer, leaving residues that are rich in beta acids. Beta acid fractions of hops can selectively inhibit specific ruminal Gram-positive bacteria that are responsible for major digestive disturbances, such as acidosis and bloat, and have a chemical structure similar to that of ionophores used in feedlot production. Use of ionophores improves efficiency of feed utilization and decreases the incidence of digestive disturbances that are a major cause of morbidity and mortality in cattle feeding operations. The objectives of this study were to evaluate the effect of beta acid extracts of hops on ruminal fermentation and diet digestibility in cattle fed high-concentrate diets and determine response to different doses of beta acid extracts of hops.
Keywords: Beef; Beta acid; Ruminal metabolism; Digestibility